Metacognition and reading comprehension : Alireza Karbalaei (2013)
This paper is aimed to argument, expand and critique some points that were held in the article “METACOGNITION AND READING COMPREHENSION” written by Alireza Karbalaei, 2010, an EFL teacher and Ph. D Graduate in ELT from the Department of English Language, Islamic Azad University. We organize the paper in three sessions. First, we explore the policies for teaching reading in the EFL; contextualizing into a more specific setting and supporting the ideas with the results from the ICFES exam. Then, we continue with the concepts of reading and reading comprehension which are focused on the way we recognize the words from a text and the way we relate those words with our previous knowledge towards making meaning out of it. Finally, we bring up the reading strategies used when approaching top-down and bottom-up processes.